Contact-dependent mechanical properties of graphene nanoribbons: An ab initio study - Dianat, Arezoo; Ryndyk, Dmitry A.; Cuniberti, Gianaurelio (Giovanni) (Nanotechnology, 2016)
The mechanical properties of graphene nanoribbons on Ni(111) surfaces with different contact sizes are investigated by means of density functional theory. For finite contact sizes, the stress behavior of graphene nanoribbons on metal electrodes is likely to be similar to that of suspended graphene, however the critical strain is not reached due to the sliding friction at the interface. The competition between frictional and external forces is responsible for the nonmonotonic stress behavior. It is indicated that the stick-slip motions of graphene on Ni(111) are as a result of applied external forces on the GNR/metal contact. Moreover, the effect of vacancies and chemical doping on the sliding friction are addressed. Graphene starts to slide on the surface under a much lower external force in the case of defected graphene, due to the weaker binding to the surface. For infinite contact sizes, a linear relationship between stress and strain are found until structural failure occurs by 11% applied strain. The corresponding critical strain for the suspended GNR (without electrodes) has been found to be 13%.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Contact; Graphene; Mechanical properties